Photodynamic therapy induces an immune response against a bacterial pathogen. (July 2012) - Huang, Ying-Ying; Tanaka, Masamitsu; Vecchio, Daniela; Garcia-Diaz, Maria; Chang, Julie; Morimoto, Yuji; Hamblin, Michael R
Photodynamic therapy (PDT) employs the triple combination of photosensitizers, visible light and ambient oxygen. When PDT is used for cancer, it has been observed that both arms of the host immune system (innate and adaptive) are activated. When PDT is used for infectious disease, however, it has been assumed that the direct antimicrobial PDT effect dominates. Murine arthritis caused by methicillin-resistant Staphylococcus aureus in the knee failed to respond to PDT with intravenously injected Photofrin ® . PDT with intra-articular Photofrin produced a biphasic dose response that killed bacteria without destroying host neutrophils. Methylene blue was the optimum photosensitizer to kill bacteria while preserving neutrophils. We used bioluminescence imaging to noninvasively monitor murine bacterial arthritis and found that PDT with intra-articular methylene blue was not only effective, but when used before infection, could protect the mice against a subsequent bacterial challenge. The data emphasize the importance of considering the host immune response in PDT for infectious disease.